Advanced Maillard Products of Disaccharides: Analysis and Relation to Reaction Conditions - Pischetsrieder, Monika; Severin, Theodor (Chemical Markers for Processed and Stored Foods, 1996)
The degradation of 1,4-glycosidic linked disaccharides, such as maltose and lactose under the condition of the Maillard reaction has been investigated. Two aminoreductones could be isolated which are derived from the 4-deoxyglucosone. Breakdown via the 1-deoxyglucosone pathway leads to 11 typical disaccharide-products. These compounds are not found in glucose reaction mixtures. All these substances can be analyzed using an HPLC system. The correlation between product composition and reaction temperature, time and pH-value has been investigated.
UnivIS-Import:2015-04-20:Pub.1996.nat.dchph.llmch.advanc